Analytical Solutions for the Study of Multielectron Transfer Processes by Staircase, Cyclic, and Differential Voltammetries at Disc Microelectrodes - Molina, A; Serna, C; Li, Q; Laborda, E; Batchelor-McAuley, C; Compton, R (2012)
Key processes in (bio)electrochemistry involve multiple electron transfers. The study of the stability of the different oxidation states and the interaction between redox centers is fundamental to understand these processes. In this paper, simple analytical equations are presented for multielectron transfer processes in cyclic voltammetry (CV) and staircase cyclic voltammetry (SCV) at disc electrodes of any size. This provides a simple simulation method for the electrochemical response without demanding computing. The use of CV and SCV, and the corresponding differential techniques, for the characterization of these redox systems is analyzed. Procedures and criteria are given for transient and stationary conditions. The theoretical results are applied to the experimental study of the reduction of anthraquinone-2-sulfonate in water on gold macro- and microdisc electrodes. © 2012 American Chemical Society.